2021
DOI: 10.3390/antiox10030371
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antioxidant Effects of Dietary Supplementation and Lifestyle Factors

Abstract: Trends relating to specific diets and lifestyle factors like physical (in) activity have formed in recent times [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This alleviates oxidative stress and inflammation and triggers the release of endorphins found after acupuncture in RA patients [ 21 ]. Moreover, studies show that fasting [ 22 ] and a rich antioxidant diet can reduce inflammation by regulating oxidative stress [ 23 ]. Studies have shown that quality of life is comparatively low in all domains (physical health, mental health, and emotional aspects) in RA patients because of fatigue, pain, stiffness, and impaired physical functioning [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This alleviates oxidative stress and inflammation and triggers the release of endorphins found after acupuncture in RA patients [ 21 ]. Moreover, studies show that fasting [ 22 ] and a rich antioxidant diet can reduce inflammation by regulating oxidative stress [ 23 ]. Studies have shown that quality of life is comparatively low in all domains (physical health, mental health, and emotional aspects) in RA patients because of fatigue, pain, stiffness, and impaired physical functioning [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given its proven positive effect on hypertension and cardiovascular health, it would be beneficial to study the effects of physical activity on the changes in exercise-related miRNAs that control the activity of IL-1β. The impact of diet and the use of food supplements on miRNA regulation of inflammation has also been considered a necessary area of study [87]. For example, in a 2019 study, obese individuals exposed to a ketogenic diet exhibited miRNA levels similar to lean subjects [88].…”
Section: Discussionmentioning
confidence: 99%
“…PE is considered a valuable non-pharmacological therapy, but it must be included in a lifestyle strategy designed to enhance overall wellbeing, in which diet also plays an important role. This combination can beneficially influence oxidative stress and inflammation levels [ 213 ].…”
Section: State Of the Artmentioning
confidence: 99%